Towards a methodology for the characterization of teachers´ Didactic-Mathematical knowledge (2015)
ABSTARCT: This research study aims at exploring the useof some dimensions and theoretical-methodological tools suggested by the modelof Didactic-Mathematical Knowledge (DMK) for the analysis,characterization and development of knowledge that teachers should have inorder to efficiently develop within their practice. For this purpose, weanalyzed the activity performed by five high school teachers, in relation to anactivity about patterns suggested in the framework of the Master of MathematicsEducation Program at University of Los Lagos, Chile. As a result of theanalysis, it becomes evident that teachers can indeed solve items related tothe common content knowledge, but have certain difficulties when they faceitems that aim at exploring other dimensions of their knowledge, for example,about extended content knowledge, of resources and means, or of the affectivestate of students.